Seroprevalensi Hepatitis B pada Pemulung Sampah di Kota Palangka Raya - Suratno Suratno; Fera Sartika (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Hepatitis B is a hepatitis B virus (HBV) infection which can exacerbate the liver and cause acute and chronic disease. The most susceptible group to hepatitis B transmission is waste pickers. This study aimed to determine: (1) the level of Hepatitis B virus infection among waste pickers in several temporary waste shelters in Palangka Raya, and (2) risk factors for hepatitis B virus infection in waste pickers in several temporary waste shelters in Palangka Raya. The observational analytic study using a cross-sectional study design was used in this research. The purposive sampling technique was carried out to involve 32 waste pickers in Palangka Raya. Examination of hepatitis B screening through HBsAg test to waste scavenger blood samples using the Rapid Test method. The results showed that the rate of hepatitis B infection based on positive HBsAg examination was 3.1% of respondents. Risk factors for transmission or exposure to hepatitis B that are directly related to the activity of garbage scavengers are not using protective equipment (PPE) gloves and bare hands waste collection, respectively 3.6% and 6.7%